Evaluasi Program Pembinaan Prestasi Atlet Renang Federasi Akuatik Indonesia (FAI) Kota Solok - Riski Rinaldi; Argantos; Syahrastani; Zulbahri; Firman; Randi Kurniawan (Jurnal Penelitian Pendidikan IPA, 2025)
The problem in the research is motivated because the achievements of Indonesian Aquatic Federation swimming athletes have not been maximized. This is suspected, because the coaching program given to athletes is not running optimally. The purpose of the study was to evaluate the coaching program for the achievements of swimming athletes of the Indonesian Aquatic Federation (IAF) Solok City. The research method is CIPP model program evaluation research with informants of administrators, coaches and swimming athletes of IAF Solok City. Data collection was obtained through observation, interviews and documentation. The results showed that, (1) Context aspect, the coaching program carried out aims to produce athletes who excel in swimming, both at the Regional, Provincial and even National levels. (2) Input aspects, there is a written management structure, already has a certified or licensed coach, a lot of good potential to become a swimming athlete, there are no adequate facilities and infrastructure, and need to be renewed, and there are only short-term training planning documents that are not arranged as training programs, (3) Process aspects, there is a written coach preparation. The implementation of the training program provided is in accordance with what the coach has prepared. (4) Product aspects, the achievements of athletes in championships that are followed such as O2SN Provincial Level, BSC and HBSC time trials, NSC, Yogyakarta national students, Igornas Provincial Level, Kejurda, Riau open and Minangkabau open. There are changes in the attitude of athletes such as discipline, courtesy, sportsmanship and a sense of caring for one another.